The effect of different nitrogen level towards the bacterial leaf blight on rice (Vegetative stage) / Mohd Hafifi Buang - Buang, Mohd Hafifi (Faculty of Plantation and Agrotechnology, 2019)
Rice (Oryza sativa L.) is cultivated in tropical and subtropical regions and become an essential food for 2.7 billion people worldwide including Malaysia. It is prone to a number of diseases. Bacterial Leaf Blight (BLB) on rice caused by pathogen Xanthomonas oryzae has been important constraints to rice production mostly in Asia. Among the factors contributing to BLB development, application of high level of nitrogen (N) is important in increased disease incidence and severity. High N levels may favor pathogen multiplication and lesion enlargement or, would increase vegetative growth of the crop, influence the microclimate in favor of the pathogen. A study to evaluate the response of BLB severity treated with different level of nitrogen and to investigate the relationship between nitrogen level and disease severity on rice during vegetative growth was implemented in Complete Randomized Design (CRD) with factorial arrangement with three replications. Treatments comprises of; 0 g N/pot, 1.0 N/pot, and 1.5 N/pot. The data on disease severity were recorded by using standard disease index published by IRRI and chlorophyll content was recorded using standard procedure. Paddy leaf was affected significantly by various rate of N. In case of bacterial leaf blight, minimum disease incidence percentage was observed when nitrogen applied @ 1.0 g N/pot in contrast to fertilizer applied @ 0 g N/pot which showed maximum disease incidence percentage. Furthermore, the most critical disease severity were recorded with zero application of N in Treatment 1 while second most critical severity was observed with 1.5 g N/pot application in Treatment 3.